2020
DOI: 10.1101/2020.04.29.068239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic feedback and stochastic partitioning during cell division can drive resistance to EMT

Abstract: Epithelial-mesenchymal transition (EMT) and its reverse process mesenchymal-epithelial transition (MET) are central to metastatic aggressiveness and therapy resistance in solid tumors. While molecular determinants of both processes have been extensively characterized, the heterogeneity in the response of tumor cells to EMT and MET inducers has come into focus recently, and has been implicated in the failure of anti-cancer therapies. Recent experimental studies have shown that some cells can undergo an irrevers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…These results suggest that the proliferative and invasive phenotype genes tend to form two ‘teams’ of mutually opposing players that can govern the emergence of phenotypic plasticity and heterogeneity in melanoma. Such ‘teams’ have been witnessed between EMT-inducing and EMT-inhibiting factors (Jia et al, 2020b), as well as those between master regulators of ‘classic’ and ‘variant’ subtypes in small cell lung cancer (Chauhan et al, 2020), elucidating a potential common design principle for regulatory networks involved in cancer cell plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the proliferative and invasive phenotype genes tend to form two ‘teams’ of mutually opposing players that can govern the emergence of phenotypic plasticity and heterogeneity in melanoma. Such ‘teams’ have been witnessed between EMT-inducing and EMT-inhibiting factors (Jia et al, 2020b), as well as those between master regulators of ‘classic’ and ‘variant’ subtypes in small cell lung cancer (Chauhan et al, 2020), elucidating a potential common design principle for regulatory networks involved in cancer cell plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…These emerging studies have revealed global epigenetic alterations and identified major factors including Zeb1, RUNX2, GRHL, and CTCF involved in reversible or stabilized EMT/MET in multiple cell lines ( 69 , 99 102 ). Besides, recent mathematical models proposed conceptually that epigenetic process may play a significant role in the irreversibility of EMT and MET, where epigenetic feedback-mediated suppression on miR-200 by Zeb1 led to the irreversibility of EMT, while epigenetic feedback-mediated suppression on Zeb1 by GRHL2 resulted in the irreversibility of MET ( 95 , 103 ). Yet this irreversible MET has been proved to be unlocked by epigenetic modification in the preliminary experiment ( 95 , 104 ).…”
Section: Therapies Targeting Emt Via Epigenetic Modificationmentioning
confidence: 99%
“…blocking access to ZEB1 promoter for EMT inducers) in inhibiting ZEB1 can enable irreversible MET, i.e. resistance of cells to undergo EMT [67,68]. Here, we assessed the impact of KLF4-mediated epigenetic silencing of SNAIL (i.e.…”
Section: Epigenetic Changes Including Klf4 Promoter Methylation Can Alter Population Distributions Along the Emt Spectrummentioning
confidence: 99%